Fabrication of feeding plate prosthesis for a six days old neonate: a case report - S, Aruna Kumari (International Journal of Dental Materials, 2019)
Feeding a new born baby with complete cleft lip and palate is a problematic pursuit because of the communication between the oral cavity and the nasal cavity. A multidisciplinary approach is needed to manage the complex problems involved in the case of such neonates and their families. The present case is of a 6-day-old neonate having complete right unilateral cleft lip and palate (Veau class C) for which palatal obturator was constructed. In this case report a stepwise simple, secure, and uncomplicated procedure for making accurate impressions, maxillary cast, and fabrication of palatal obturator in infants with cleft lip and palate have been presented.